Deep Vein Thrombosis Prophylaxis in Trauma Patients. (15th May 2011) - Toker, Serdar; Hak, David J.; Morgan, Steven J.
Abstract : Deep vein thrombosis (DVT) and pulmonary embolism (PE) are known collectively as venous thromboembolism (VTE). Venous thromboembolic events are common and potentially life-threatening complications following trauma with an incidence of 5 to 63%. DVT prophylaxis is essential in the management of trauma patients. Currently, the optimal VTE prophylaxis strategy for trauma patients is unknown. Traditionally, pelvic and lower extremity fractures, head injury, and prolonged immobilization have been considered risk factors for VTE; however it is unclear which combination of risk factors defines a high-risk group. Modalities available for trauma patient thromboprophylaxis are classified into pharmacologic anticoagulation, mechanical prophylaxis, and inferior vena cava (IVC) filters. The available pharmacologic agents include low-dose heparin (LDH), low molecular weight heparin (LMWH), and factor Xa inhibitors. Mechanical prophylaxis methods include graduated compression stockings (GCSs), pneumatic compression devices (PCDs), and A-V foot pumps. IVCs are traditionally used in high risk patients in whom pharmacological prophylaxis is contraindicated. Both EAST and ACCP guidelines recommend primary use of LMWHs in trauma patients; however there are still controversies regarding the definitive VTE prophylaxis in trauma patients. Large randomized prospective clinical studies would be required to provide level I evidence to define the optimal VTE prophylaxis in trauma patients.